2008
DOI: 10.1021/jp709886y
|View full text |Cite
|
Sign up to set email alerts
|

Ni@Pt Core−Shell Nanoparticles:  Synthesis, Structural and Electrochemical Properties

Abstract: Core-shell nanoparticles composed of a nonnoble metal core and a noble metal shell are of great significance in many areas including chemical catalysis, optical detection, and magnetic separation. Through a modification of the commonly used polyol process, Ni@Pt core-shell nanoparticles that are less than 10 nm in total size and have a very thin Pt shell can be fabricated by a sequential reduction approach. The prepared core-shell nanoparticles were characterized with TEM, XRD, molecular dynamics (MD) simulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
74
1
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(82 citation statements)
references
References 39 publications
3
74
1
4
Order By: Relevance
“…Higher electrocatalytic properties from Pt-alloys as well other noble metals-alloys over Pt, have been related with different phenomena broadly classified as: i) structural, ii) electronic and iii) surface sensitive factors [8,9]. For example, different studies have revealed that modifying the M 1 eM 2 distance through lattice contraction or expansion due to alloying effect, may decrease the OH adsorption energy on Pt-alloy increasing ORR activity [10,11]. However, it is necessary to mention that both geometric and electronic effects are intimately entrenched, thus, separating these effects and assessing their relative importance in the electrocatalytic activity and reaction mechanism, is rather difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Higher electrocatalytic properties from Pt-alloys as well other noble metals-alloys over Pt, have been related with different phenomena broadly classified as: i) structural, ii) electronic and iii) surface sensitive factors [8,9]. For example, different studies have revealed that modifying the M 1 eM 2 distance through lattice contraction or expansion due to alloying effect, may decrease the OH adsorption energy on Pt-alloy increasing ORR activity [10,11]. However, it is necessary to mention that both geometric and electronic effects are intimately entrenched, thus, separating these effects and assessing their relative importance in the electrocatalytic activity and reaction mechanism, is rather difficult.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Besides the use of carbon-supported Pt alloys, several recent reports suggest core-shell nanoparticles as catalyst materials for PEM fuel cells. The various methods suggested to prepare such catalysts include chemical synthesis using reducing agents for the preparation of, for example, Pt@Fe, [7] Au@Pt/C, [8] and Ni@Pt [9] core@shell catalysts, redox displacement of the core by a more noble metal forming the shell to yield, for example, Co@Au [10] and Fe@Pt [11] catalysts, and redox displacement of a layer of Cu formed by underpotential deposition (UPD) on a core to yield a monolayer of Pt in, for example, Au@Pt [12] and Pd@Pt. [13] Redox displacement of Cu has also been used with single crystals to form a monolayer of Pt [13] and on thermally segregated alloy cores to yield, for example, NiAu@Pt.…”
Section: Introductionmentioning
confidence: 99%
“…Electrochemical behaviors of materials are very sensitive to their surface composition and structures [32]. 36 …”
Section: Resultsmentioning
confidence: 99%
“…The formation of the core-shell structure has been elucidated by various techniques, including transmission electron microscopy (TEM) and electrochemical techniques. Although the Co core -Pt shell particles have a much reduced content of Pt, they exhibit significantly enhanced catalytic activity toward oxygen reduction as compared to pure Pt catalyst, showing their great promise in solving the problem of the high demand for precious platinum metal in the cathodes of state-of-the-art PEM fuel cells [32].…”
Section: Introductionmentioning
confidence: 99%